2021
DOI: 10.1093/molbev/msab159
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mutation Rate, Relaxed Selection, and the “Domino Effect” are associated with Gene Loss in Blattabacterium, A Cockroach Endosymbiont

Abstract: Intracellular endosymbionts have reduced genomes that progressively lose genes at a timescale of tens of million years. We previously reported that gene loss rate is linked to mutation rate in Blattabacterium, however, the mechanisms causing gene loss are not yet fully understood. Here, we carried out comparative genomic analyses on the complete genome sequences of a representative set of 67 Blattabacterium strains, with sizes ranging between 511kbp and 645kbp. We found that 200 of the 566 analysed protein-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…On the other hand, and similar to other omnivorous animals, they harbour in their hindgut (the posterior part of the gut) a complex microbiota. The complete genome of at least 70 Blattabacterium strains have been sequenced, and their metabolisms inferred, confirming their monophyletic origin in all cockroaches as well as their essentiality in hosts' physiology [48][49][50][51]. Besides, the gut microbiota has also been characterized in several species, both at taxonomic and functional levels.…”
Section: The Dual Symbiotic System In Cockroachesmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, and similar to other omnivorous animals, they harbour in their hindgut (the posterior part of the gut) a complex microbiota. The complete genome of at least 70 Blattabacterium strains have been sequenced, and their metabolisms inferred, confirming their monophyletic origin in all cockroaches as well as their essentiality in hosts' physiology [48][49][50][51]. Besides, the gut microbiota has also been characterized in several species, both at taxonomic and functional levels.…”
Section: The Dual Symbiotic System In Cockroachesmentioning
confidence: 77%
“…Thus, 200 out of the 566 protein-coding genes under study were lost in at least one lineage, while 25 were lost independently from 10 to 24 times. Such losses affect the genes related to the biosynthesis of amino acids and cofactors to a greater extent, while those involved in nitrogen metabolism are retained [49].…”
Section: The Essential Role Of Blattabacteriummentioning
confidence: 99%
“…This is consistent with previous research in Blochmannia endosymbionts identifying lineage‐specific gene loss largely due to relaxed selection constraints and genetic drift (Williams & Wernegreen, 2015 ). Similarly, in cockroach Blattabacterium endosymbionts, Kinjo et al ( 2021 ) found that gene loss was lineage‐specific, and that some genes showed parallel gene loss across multiple Blattabacterium lineages.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in cockroach Blattabacterium endosymbionts, Kinjo et al (2021) found that gene loss was lineage-specific, and that some genes showed parallel gene loss across multiple Blattabacterium lineages.…”
Section: Does Host Demography Shape Endosymbiont Evolution?mentioning
confidence: 93%
“…Strains that stop performing these costly functions and eventually lose the corresponding genes have a local advantage [15]. While gene loss due to drift is known in bacteria, especially in host-restricted taxa [26,27], genome reduction also occurs in bacteria with very large effective population sizes, such as the marine-dwelling Synechococcus and Roseobacter [28,29]. Selective pressure to lose genes could be due to general genome streamlining caused by deletion bias observed in bacterial genomes [30], a possible way to purge them of selfish genetic elements [31].…”
Section: Costs Of Public Good Genesmentioning
confidence: 99%